2013
DOI: 10.1161/hypertensionaha.111.00157
|View full text |Cite|
|
Sign up to set email alerts
|

Angiotensin Receptor Agonistic Autoantibody-Mediated Soluble Fms-Like Tyrosine Kinase-1 Induction Contributes to Impaired Adrenal Vasculature and Decreased Aldosterone Production in Preeclampsia

Abstract: Preeclampsia (PE) is a life-threatening hypertensive disorder of pregnancy associated with decreased circulating aldosterone levels. However, the molecular mechanisms underlying aldosterone reduction in PE remain unidentified. Here we demonstrate that reduced circulating aldosterone levels in the preeclamptic women are associated with the presence of angiotensin II type 1 receptor agonistic autoantibody (AT1-AA) and elevated soluble Fms-like tyrosine kinase-1 (sFlt-1), two prominent pathogenic factors in PE. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
4
39
0
Order By: Relevance
“…6a). Consistent with earlier in-vivo animal studies [11], the short-term presence (24 h) of AT 1 -AA at a low level (0.5 mg/ml) stimulated both cellular ALD secretion and cell growth (Fig. 6a and Fig.…”
Section: Activation Of Angiotensin II Type 1 Receptor By At 1 -Aa Dirsupporting
confidence: 91%
See 2 more Smart Citations
“…6a). Consistent with earlier in-vivo animal studies [11], the short-term presence (24 h) of AT 1 -AA at a low level (0.5 mg/ml) stimulated both cellular ALD secretion and cell growth (Fig. 6a and Fig.…”
Section: Activation Of Angiotensin II Type 1 Receptor By At 1 -Aa Dirsupporting
confidence: 91%
“…Recently, some interesting findings support a model in which AT 1 -AA-mediated sFlt-1 elevation accounts for a reduction of ALD production by impairing adrenal gland vasculature in the pregnant mice with hypertension and proteinuria [11]. However, effects of AT 1 -AA on ALD production, independent of pregnancy, especially in terms of the impact of long-term circulation of AT 1 -AA, were not examined in the study, and the correlation of AT 1 -AA to ALD in preeclampsia patients remains unknown.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Volume expansion prevails in pregnancy, while tight control by the renin‐angiotensin system (RAS) and consecutive aldosterone production via tubular Na + sensing1 is uncoupled in pregnancy 2, 3, 4. In pregnancy, aldosterone levels are high despite plasma volume expansion and also less responsive to increased Na + intake.…”
Section: Introductionmentioning
confidence: 99%
“…Being a major pathogenic factor, AngII can induce cardiac fibroblasts proliferation, increase collagen synthesis, produce myocardial fibrosis, and play a very important role in the activation and the development of various cardiovascular diseases, such as chronic heart failure, myocardial infarction, arrhythmia and others [37]. Many studies have confirmed that many drugs can protect myocardium through inhibition of the biological effect of AngII.…”
Section: The Effects Of Complexes 1 and 2 On Cultured Cardiac Fibroblmentioning
confidence: 99%